Edukasi Posisi Persalinan Sesuai Standar Asuhan Persalinan Normal Pada Ibu Hamil - Mutmaina, Mutmaina (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2022)
The squatting position is the central position used by the community in Kalora Village during the delivery process. This position has become a tradition of providing benefits if followed and vice versa. This study aimed to improve mothers' knowledge, attitude, and action in choosing a comfortable delivery position. The method used was education through counseling and practical exercises for one day, using leaflets, mats, and other equipment. The participants comprised ten pregnant women, and the activity occurred in Hamlet III, Kalora Village. The results showed increased knowledge and attitude and better adherence to standard normal delivery care in choosing a delivery position. However, some mothers still had to choose a position that was not based on their preference due to cultural factors and experiences influencing pregnant women in decision-making. In conclusion, there was an improvement in knowledge and attitude, but not necessarily in action. Therefore, it is recommended that midwives in the village always provide education to pregnant women, especially about delivery positions